„Caillié contra Barth in Timbuktu oder Vulnerabilität vs. Resilienz der endogenen Technologie ums Schießpulver. Eine postkoloniale Literaturkritik am Forschungs- und Entdeckungsdiskurs“ - KPAO SARE, MINSI CONSTANT (My University, 2025)
The (mainly African) postcolonial research literature has increasingly empha-sised that Western European writings had developed a series of Eurocentric strategies based on data manipulation, distortion and intimidation that under-mine the remarkable resilience of African knowledge systems. The starting thesis of these reflexions is that only a decolonial research perspective drawing exclusively on texts from the Global South can appreciate the value of indi-genous and endogenous knowledge (s. Seepe 2000; Ndlovu-Gatshen 2014). Through a contrastive analysis of two travelogues, namely René Caillié’s Tra-vels Through Central Africa to Timbuctoo (1830) and Heinrich Barth’s Travels and Discoveries (1857), this paper attempts to substantiate this assumption in a more nuanced way. While Caillié, for example, was a child of his time and spread the general opinion in Europe about the supposed backwardness of indigenous technologies, Barth, as a follower of the Berlin geographer Carl Ritter (1779–1859), endeavoured to emphasise the creativity of Africans. In Barth’s discourse on the discovery of gunpowder in Africa, there is no mis-trust, but rather forms of resilience of traditional folk culture and resistance to the colonial project and the colonial incorporation of endogenous knowledge in the so-called global knowledge.
Keywords: Resilience- Technological encounter - Postcolonial critique - Gunpowder - Heinrich Barth - René Caillié